Pengaruh Pelayanan, Kualitas Produk Dan Loyalitas Terhadap Kepuasan Konsumen Islam di Indomaret Hibrida III Kota Bengkulu - Fitra Sanjaya; Yosi Arisandi; Kustin Hartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of service, product quality and loyalty on Islamic consumer satisfaction in Indomaret Hibrida III Bengkulu City. This research was carried out at Indomaret Hybrid III, Bengkulu City. This type of research is quantitative research with the approach used is a descriptive approach. The population in this study is consumers of Indomaret Hybrid III Bengkulu City. The technique used in sampling is a non-probability sampling technique with a total of 90 samples. The data collection techniques used in this study are by conducting observations, distributing questionnaires and documentation to find information about Indomaret Hybrid III Consumer Satisfaction in Bengkulu City. The results of the study showed that service quality had a positive and significant effect on customer satisfaction in Indomaret Hibrida III Bengkulu City, namely (14,613 > 2.02809) and sig < a (0.000 < 0.050). So it can be concluded that the Service Quality variable has a positive and significant effect on Customer Satisfaction. The Product Quality variable (X2), shows t count > t table, namely (2,473 > 2.02809) and sig < a (0.018 < 0.050). So it can be concluded that the Product Quality variable has a positive and significant effect on Customer Satisfaction. The Customer Loyalty variable (X3), shows t count t table, namely (2,525 > 2.02809) and sig < a (0.016 < 0.050). So it can be concluded that the Customer Loyalty variable has a negative effect on Customer Satisfaction. From the results of data management, it can be concluded that all independent variables, namely the variables of Service Quality (X1), Product Quality (X2) and Customer Loyalty (X3) simultaneously or together have a significant effect on the dependent variable, namely Customer Satisfaction